Tiny T. Rex and the very dark dark - Stutzman, Jonathan (Chronicle Books, 2020)
Tiny T. Rex and his friend Pointy are planning a campout in the backyard, but they are both worried that the dark will be altogether too dark, so they plan on bringing a night light with them -- but when the night light does not work they bravely open their eyes and discover the stars above.